Furcation diagnosis - Müller, Hans-Peter; Eger, Thomas (Journal of clinical periodontology, 1999)
One of the most important and at present unsolved problems in clinical periodontology is the predictable successful treatment of periodontitis-affected furcations of multirooted teeth. Since several therapeutic approaches are proposed, i.e., conservative, resective or regenerative, a proper diagnosis of these lesions is demanding. The aim of the present article is to review the current information on the impact of a proper diagnosis of a furcational lesion as well as tooth morphology on decision making with regard to different treatment modalities and to emphasize the need for a detailed clinical, radiographical and intraoperative diagnosis of the furcation lesion beyond the usually performed diagnosis of the degree of furcation involvement.
Elektronische Reproduktion der Druck-Ausgabe
First published: 09 October 2003
Gesehen am 24.02.2021